Desarrollo de las inteligencias múltiples físico-cinestésica y lógica-matemática y su relación en el rendimiento escolar de las niñas y niños del primer año de educación general básica del centro educativo “José Alejo Palacios” de la ciudad de Loja, período escolar 2011-2012 - Medina Salinas, Delia María (2014)
This research addresses the development of multiple intelligences physical - kinesthetic, logical -mathematical implemented by teachers in the school performance of children from the first year of General Basic Education school "Alejo José Palacios" Loja city, period 2011-2012 The importance of the theory of multiple intelligences is set in the first year of basic general education because it responds to the ability to solve problems of life, is located in various brain areas and interconnected, what was once considered innate, static. The new concept proposed by Gardner makes intelligence as a set of skills and abilities that can be developed and not denied the genetic component. Physics-kinesthetic, includes specific physical skills such as coordination, balance, dexterity, strength, flexibility and speed, as well as self-perceptive capabilities, and mathematical logic, including categorization, classification, inference, generalization, the calculation and display hypotheses. The overall objective was raised to analyze the development of multiple intelligences physical-kinesthetic, logical-mathematical implemented by teachers in the school performance of children from the first year of General Basic Education school "Alejo José Palacios" in the city of Loja. The research used the following methods: deductive, inductive, analytic techniques used were the literature, surveys and observation sheet for teachers, and observation sheet for children. It was concluded that multiple intelligences are a viable and effective alternative for the development of physical skills kinesthetic and logical-mathematical, not only cognitive, motor and emotional but, implemented by teachers in the school performance of children, the school performance and management theories of multiple intelligences, is absolutely necessary to train teachers and students through teaching techniques and strategies based on mental processes, and recommend to the teachers make use of multiple intelligences and then evaluate students for general and specific levels, to achieve these gains, there is the seminar workshop, aimed at training.